226 Changes in sleep amount and sleep quality due to the COVID-19 pandemic confinement associate with ratings of health and stress. (3rd May 2021) - Jones, Christopher; Kaizi-Lutu, Marc; Cordoza, Makayla; Mange, Ami; Dinges, David
Abstract: Introduction: In March 2020, an unprecedented number of individuals were confined to their homes in an effort to stem the spread of the novel Coronavirus (Covid-19), however the impact of this confinement on health and behavior is unknown. Long-duration confinement studies have found effects on homeostatic biology and neurobehavioral functions, including reduced sleep durations. This study evaluated how confinement due to Covid-19 has impacted health and stress through changes in sleep. Methods: The Anonymous Survey on Confinement during the COVID-19 Pandemic was available online to any individual ≥18 years of age through the Penn Medicine Clinical Research webpage on May 14, 2020 and the data presented are through October 24, 2020. The survey collected self-reported information on demographics, the amount and quality of sleep, as well as ratings of health and stress. To determine the impact of confinement on these domains, participants were asked to answer questions relative to pre-confinement levels. To test associations between sleep amounts and sleep quality on health and stress, generalized linear models were used and adjusted for age, sex, and race. Results: N=228 participants (n=180 female [79.0%]) were on average 45.0±17.1 years of age. During confinement relative to pre-confinement, 41.7% of participants reported sleeping more, 37.3% reported sleeping the same amount, and 21.0% reported less sleep, while 14.0% reported better sleep quality, 47.4% the same, and 38.6% worse quality of sleep relative to pre-confinement. Ratings of worse health during confinement were associated with both reduced sleep amount (β=0.695; P<0.0001) and worse sleep quality (β=0.532; P=0.0002). Lower stress ratings were associated with increased sleep amount (β=0.734; P=0.034), better sleep quality (β=1.396; P=0.0002), better health ratings (β=-0.079; P=0.0045). Conversely, worse sleep quality was associated with higher stress ratings (β=-1.086; P=0.0007). Conclusion: The confinement resulting from the COVID-19 pandemic has impacted the amount and quality of sleep and good sleep may help to reduce stress and maintain health. These findings highlight the need to further examine how long-term confinement influences human health and behavior and warrant examining what factors or life-style behaviors promote resilience to the negative effects of confinement. Support (if any): CWJ supported by NHLBI NRSA (T32 HL007713).